Toward More Accountable PPPs : A Review of the Development, Implementation, and Post-Implementation Experience of Improved Disclosure Practices in PPPs in Ghana, Honduras, Kenya, and Nigeria - World Bank (World Bank, Washington, DC, 2021)
In the face of declining fiscal space and the need to build back better after the Coronavirus (COVID-19) pandemic, governments are turning to public-private partnerships (PPPs) to deliver infrastructure assets and services. Disclosure of information plays an important role in PPP programs. Several clients of the World Bank Group, including those with well-established PPP programs, currently do not disclose PPP information in a structured way throughout the project life cycle. Responding to these challenges, the World Bank developed a series of knowledge products to understand disclosure in PPPs, as well as to provide tools to governments for improving PPP disclosure. Post implementation of national PPP disclosure frameworks in the pilot countries, it became important to document the process, as well as assess the experience and perceptions related to the changed disclosure environment culminating in the disclosure of information via public-facing web portals. To support this task, a study was carried out over 2019-2020 to capture the enhanced disclosure environment, understand the perceptions of stakeholders vis-à-vis structured disclosure, identify what was working well, as well as indicate areas for improvement. This paper is a culmination of this effort to document the process and analyze the experience gained from the four-country pilot carried out in Ghana, Honduras, Kenya, and Nigeria. Section 1 of the paper provides the general background within which PPP disclosure is located, as well as the key elements of the World Bank’s Framework for Disclosure in PPPs. Section 2 documents the process followed in developing and implementing customized national frameworks in the pilot countries.